Chelation-Assisted Regioselective Catalytic Functionalization of C–H, C–O, C–N and C–F Bonds - Kakiuchi, Fumitoshi; Kochi, Takuya; Murai, Shinji (Synlett, 2014)
Transition-metal-catalyzed functionalization of unreactive carbon bonds such as C–H, C–O, C–N, and C–F bonds has been extensively studied over the last two decades. In this account we describe our studies on chelation-assisted catalytic transformations of unreactive carbon bonds in aromatic and olefinic compounds. Various C–C bond forming reactions are achieved by catalytic addition of C–H bonds to alkenes and alkynes, and via coupling reactions such as those of C–H, C–O, C–N, and C–F bonds with boronic esters. Methods for the conversion of C–H bonds into C–Si and C–X (X = halogen) bonds are also developed. The C–C bond forming reactions are applied to short syntheses of polycyclic aromatic hydrocarbons.1 Introduction2 Conversion of C–H Bonds into C–C Bonds2.1 C–H Alkylation2.1.1 Scope and Limitations2.1.2 Mechanistic Studies2.2 C–H Arylation2.3 C–H Alkenylation2.4 Introduction of Carbonyl Functionality via C–H Bond Cleavage3 Conversion of Aromatic C–O, C–N and C–F Bonds into C–C Bonds by Coupling with Organoboronates3.1 Coupling with Organoboronates via Aromatic C–O Bond Cleavage3.2 Coupling with Organoboronates via Aromatic C–N Bond Cleavage3.3 Coupling with Organoboronates via Aromatic C–F Bond Cleavage4 Introduction of Heteroatoms at C–H Bonds4.1 Silylation of C–H Bonds4.1.1 Silylation of Aromatic C–H Bonds with Hydrosilanes4.1.2 Silylation of Benzylic C(sp3)–H Bonds with Hydrosilanes4.1.3 C–H Silylation with Vinylsilanes4.2 Aromatic C–H Halogenation by Palladium-Catalyzed C–H Bond Cleavage and Electrochemical Oxidation4.2.1 C–H Chlorination and Bromination4.2.2 C–H Iodination and One-Pot C–H Iodination/Suzuki–Miyaura Coupling by ON/OFF Switching of Electric Current5 Applications of C–H Functionalization in Short Syntheses of Polycyclic Aromatic Hydrocarbons (PAHs)5.1 Convenient Synthesis of Multiarylanthracenes5.2 Short Synthesis of Alkyl-Substituted Anthracenes and Pentacenes5.3 Short Synthesis of Dibenzo[a,h]anthracenes and Picenes6 Conclusions
Keywords: alkylation; arylation; alkenylation; introduction of carbonyl groups; halogenation; polycyclic aromatic hydrocarbons